CRIMINOLOGICAL REVIEW OF CHILDREN WHO COMMIT MURDER AGAINST THEIR FAMILIES - Hudaefah, eva; Irawan, H.Benny; Fajar, M.Noor (Universitas Dharmawangsa Medan, 2026)
Adolescents often engage in criminal acts, a phenomenon referred to as Juvenile Delinquency. Crimes committed by juveniles are generally minor offenses that mostly cause material harm. However, there are also cases where juveniles commit serious crimes such as murder. What is particularly concerning is that in some cases, the murder is not committed against strangers, but rather involves members of the juvenile’s own family.Problem Identification in This Juridical Research What are the factors that lead juveniles to commit murder against their family members? How can juvenile-perpetrated familial murder be addressed and prevented? This study uses a qualitative research method with a normative juridical approach This study explains, first, the factors that lead children to commit acts of murder against their family, using social control theory as the analytical framework. It was found that the most dominant factor is the family's role in child-rearing.Second, efforts to address crimes committed by children who murder family members involve both penal and non-penal approaches, with a greater emphasis on non-penal measures to prevent the recurrence of similar offenses.The conclusion of this study is that juvenile-perpetrated murder against family members is influenced by both internal and external negative factors. The prevention and control of crimes committed by children should not be the sole responsibility of the state; rather, society must also play an active role in educating children as part of non-penal efforts to prevent juvenile crime.